Environmental scleroderma: the evidence for putative triggers - Mayes, Maureen (Henry Stewart Talks, 2007)
Occupational or environmental exposures with the subsequent development of systemic sclerosis (SSc, scleroderma), Exposure to organic solvents and silica dust as a risk factor for SSc, Occurrence of scleroderma-like conditions in an epidemic fashion following known exposures, Demonstration of exposure to ingested or intravenous substances resulting in severe and long lasting dermal fibrosis
Updated at 2018/01/31